Improving winter wheat grain yield and nitrogen use efficiency using nitrogen application time and rate. Issue 1 (3rd March 2021) - Aula, Lawrence; Omara, Peter; Oyebiyi, Fikayo B.; Eickhoff, Elizabeth; Carpenter, Jonathan; Nambi, Eva; Fornah, Alimamy; Raun, William R.
Abstract: Preplant nitrogen (N) application, which involves placing nutrients in the soil before seeding, has been an integral part of crop production systems for decades. Some producers are known to apply N at least 21 d before planting. This may increase N loss and lower grain yield. This study evaluated the effect of timing and rate of N application on winter wheat ( Triticum aestivum L.) grain yield and N use efficiency (NUE). An experiment with a factorial arrangement of treatments was set up in a randomized complete block design with three replications. Treatments included four N rates (0, 45, 90, and 135 kg ha –1 ) with each applied 7 or 30 d before planting, and at Feekes 5 (FK5 ). Grain N was analyzed using LECO CN dry combustion analyzer. The difference method [Grain N from (fertilized plot – check plot)]/N applied was used to compute NUE. Nitrogen application rate significantly affected grain yield ( P  ≤ .01). Although the rate may be temporally and spatially variable, approximately 90 kg N ha –1 was required to obtain yields that differ markedly from the check. Mid‐season applied N (FK5 ) had similar yields to preplant applied N in two of four site‐years and significantly increased yield at one site in 2020. Out of two sites, the timing of N application had a substantial effect on NUE in both years ( P  ≤ 0.11). In this case, NUE was increased by as much as 9.5% for midseason applied N compared to 30 d before planting N application time.